Gambaran Kepribadian Hardiness Atlet Paralympic Atletik Lari Cepat - Gretty Wida Kinanthi; Miftakhul Jannah (Jurnal Psikologi Teori dan Terapan, 2016)
This research was motivated by a phenomenon of paralympic athletes with physical, visual, hearing and intellectual dissabilities that were demanded to keep confident and overcome problems. Stress often happens to athletes when the match is in progress so this stress causes failure on their competition and they are demanded to come up again after failure. Athletes need a tendency of hardiness personality to overcome every problem in the match so the atheletes can gain an achievement. The purpose of this research was to describe a paralympic athlete’s tendency of hardiness personality. This research used qualitative research with case-study method. A paralympic athelete who had international achievement in 200 and 400-meter sprints was recruited as the participant in this research. Data were collected using interviews, observations and document reviews which then analyzed by using thematic analysis. The results showed that the participant had tendency of hardiness personality shown by his understanding of the purpose of life, involving his self in daily activities, and controlling each of his problem. The participant also had optimism and ready to take the challenge.